A new C11b-type high entropy refractory metal silicide to improve MoSi2 mechanical properties more easily. (September 2022) - Guo, Ziqiang; Zhang, Laiqi; Qiao, Yi; Gao, Qiang; Xiao, Zepeng
Abstract: MoSi2 has two crystal structures including tetragonal C11b and hexagonal C40, and C11b -MoSi2 shows better mechanical properties normally. However, it is difficult to design and prepare C11b -type high entropy refractory metal silicides (HERMS), only C40-type HERMS have been reported up to now. In this study, (Mo0.33 W0.33 Re0.33 )Si2, (Mo0.25 W0.25 Re0.25 Cr0.25 )Si2, (Mo0.25 W0.25 Re0.25 V0.25 )Si2 and (Mo0.2 W0.2 Re0.2 Cr0.2 V0.2 )Si2 were successfully designed and synthesized with in-situ reactively hot pressing by spark plasma sintering (SPS). X-ray diffraction (XRD) shows that all these materials have a single-phase C11b crystal structure, which is the first discovery of C11b -type high entropy refractory metal silicides. The existent elements are uniformly distributed and some dislocations were formed in (Mo0.2 W0.2 Re0.2 Cr0.2 V0.2 )Si2 sample. It is found that (Mo0.2 W0.2 Re0.2 Cr0.2 V0.2 )Si2 has a higher Vickers hardness (13.31 GPa) and fracture toughness (3.16 MPam 1/2 ) than MoSi2 and previously reported C40-type HERMS. This study would further extend the HERMS material system and improve the fracture toughness of MoSi2 . Graphical abstract: Image, graphical abstract